A Study on the Challenges and Issues Faced by Inexperienced New Teachers in a New Nation: A case Study on Teachers Involved in Literacy and Numeracy Education in South Sudan - Francis, Mark Taban (Journal of Education and Practice, 2026)
Purpose: This study investigated the pedagogical practices, perceptions, and challenges of unskilled teachers involved in literacy and numeracy instruction in South Sudan. Methodology: Using a quantitative research design, the study collected data from 65 respondents across various secondary school types and locations. Questionnaires and formal interviews were administered to capture teachers’ perceptions of the newly introduced competence-based curriculum promoted by the government. The study aimed to identify ways of strengthening pedagogical knowledge and instructional skills through a contextualized training intervention. Findings: Key findings show that teachers consider qualifications, experience, training, monitoring and supervision, lesson planning, teaching aids, and appropriate teaching methods as essential factors for improving education quality. Unique Contribution to Theory, Policy and Practice: The uniqueness or important of the Gestalt or Whole Teacher Professional Development (WTPD) framework in this study lies in its holistic response to the complex realities faced by unskilled teachers in South Sudan. Unlike traditional Professional Development models that prioritize technical skills alone, WTPD integrates teachers’ attitudes, emotions, self-concept, and professional identity—critical factors in a post-conflict context marked by low qualifications, limited mentorship, and weak collegial support. By addressing the “whole teacher,” this approach nurtures reflective practice, confidence, and learner-centered mindsets; helping beginner teachers in literacy and numeracy develop not only instructional competence but also resilience and ethical commitment essential for effective teaching in fragile settings.